SOME ASPECTS OF TRANSLATION OF TECHNICAL TERMS AND RULES OF THE CIVIL AVIATION - Primashev , Нурзада Маханбетович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
This article discusses some aspects translation of Kazakh technical terms of civil aviation. According to the author, the translation of technical terms require not only linguistic, technical knowledge. Wrong translation of technical terms and phrases can lead to accidents and malfunctions.